Global journalism : topical issues and media systems - De Beer, Arnold S., ....-; Merrill, John Calhoun, 1924-2012 (London : Allyn and Bacon, 2009)
Thoroughly reviewed, with new chapters and several new authors, Global Journalism addresses the most pertinent issues and problems in today's global journalism. This new edition recognizes the vast and rapid changes taking place in global journalism across media systems on all continents. Its three interlinking parts offer an overview of the present state of media and journalism theory; a critical analysis of the main issues confronting global journalists, media organizations, audiences, and others in the media world; and a focus on the media of the world's eight major journalism and media regions. Global Journalism has established itself over a quarter of a century as a trusted authority on international media. The new edition carries that reputation further into the 21st Century for a new generation of journalism and media scholars, students, and media professionals.
Raeymaeckers, Karin
Keywords: Go international; International office; Journalistiek